Medical Dispute Resolution Based on RME Data Through Restorative Justice - Bharata, Yoseph; Zamroni, Mohammad; Pramono, Budi (Universitas Muhammadiyah Sumatera Utara, 2024)
This research aims to analyze the benefits of Medical Record Encryption (MRE) data in legal safeguards for physicians and patients, while also investigating the trajectory of medical dispute resolution through the lens of Restorative Justice, employing the utilization of MRE data. Framed within the contextual backdrop, this study responds to the imperative for further exploration into the pivotal role of MRE data in resolving cases of medical malpractice, with the overarching objective of contributing to the advancement of equitable and forward-looking strategies in medical dispute resolution. Employing a normative juridical research approach, this study discerns the significance of MRE data security and its implications in the legal responsibilities’ incumbent upon MRE custodians. Additionally, this study posits that the Restorative Justice approach, coupled with MRE data, can manifest as an efficacious methodology in comprehending, preempting, and fortifying the dynamics of medical disputes, thereby fostering the rapport between healthcare practitioners and patients. Consequently, the integration of MRE data in medical dispute resolution via the Restorative Justice paradigm has the potential to heighten legal protection, reinforce medical integrity, and enhance the overall efficiency of the healthcare system